Equilibrium states on higher-rank Toeplitz non-commutative solenoids. (November 2020) - AFSAR, ZAHRA; AN HUEF, ASTRID; RAEBURN, IAIN; SIMS, AIDAN
Abstract : We consider a family of higher-dimensional non-commutative tori, which are twisted analogues of the algebras of continuous functions on ordinary tori and their Toeplitz extensions. Just as solenoids are inverse limits of tori, our Toeplitz non-commutative solenoids are direct limits of the Toeplitz extensions of non-commutative tori. We consider natural dynamics on these Toeplitz algebras, and we compute the equilibrium states for these dynamics. We find a large simplex of equilibrium states at each positive inverse temperature, parametrized by the probability measures on an (ordinary) solenoid.